ANALISIS PENGARUH KEUNGGULAN PRODUK, EFEK KOMUNITAS, TERHADAP SIKAP MEREK DAN IMPLIKASINYA TERHADAP LOYALITAS PELANGGAN (Studi Kasus Warung Sate Sapi Pak Kempleng 1 di Kota Semarang) - Rochmawati, Opi; Widiyanto, Ibnu (Diponegoro Journal of Management, 2013)
This study aims to determine how big the influence product excellence, community effect and attitude towards brand of the customer loyalty on beef satay foodstall in Pak Kempleng 1 Semarang. And this research also aims to analyze the most dominant factors that influence on customer loyalty of beef satay foodstall in Pak Kempleng 1 Semarang.            The population used in this study is consumer of beef satay foodstall in Pak Kempleng 1 Semarang. The sample in this study are 100 respondents and the technique used is non-probability sampling technique with the approach purposive sampling.            The result showed that excellence product and community effect have positive and significant impacts on attitude towards brand. Further attitude towards brand, the excellence product and community effect have also positive and significant impacts on customer loyalty. The most dominant variable of model 1 is the excellence product, while for model 2, attitude towards brand is the highest influence on customer loyalty.